Design of circularly polarized rectenna with harmonic rejection capabiltity at 2.45 GHz for microwave energy transfer - Ahmed, Sharif Ahmed Qasem (2017)
Nowadays, with the fast development in wireless devices, microwave energy transfer in which energy is transmitted from one point to another without wires, becomes more vital. There are many applications in which microwave energy transfer technology can be utilized such as smart healthcare, environmental monitoring, and home automation. Microwave energy transfer has the advantages of easy communication and lower cost compared to traditional transmission mediums. A rectifying antenna or rectenna which consists of receiving antenna, rectifier, matching network, and output DC filter, is an important element in microwave energy transfer. The antenna receives RF signals that are converted from alternative current (AC) into usable direct current (DC) by the rectifying circuit. Rectifying diodes have nonlinear behavior which generates harmonics and degrades RF-to-DC conversion efficiency of the rectenna. Harmonic rejection filter is used to suppress these harmonics. However, adding harmonic rejection filter increases the size and cost of the rectenna. Antennas with harmonic rejection is used to replace the harmonic rejection filter. However, the proposed antennas have a low gain which degrades rectenna conversion efficiency. To increase the amount of collected RF signals, circular polarization, dual-band and broadband operation are adopted but these techniques increase the size and design complexity. This thesis proposed a rectenna design with harmonics rejection and circular polarization at 2.45 GHz to enhance the RF-DC conversion efficiency. The harmonic rejection capability is achieved using triangular aperture coupling slot. The circular polarization property is achieved with a single feed line which reduces the size and design complexity. The aperture coupled antenna is simulated with an air gap to enhance the gain, using Computer Simulation Technology (CST). The voltage doubler rectifier is simulated with a fast switching HSMS286B Schottky diode, using Advance Design System (ADS). The fabrication process is carried out using a low-cost 4.4 permittivity FR-4 substrate. The antenna can reject harmonics up to 10 GHz with -50 dB return loss, 7 dB gain, 1.5 dB axial ratio and 40.8% axial ratio bandwidth. The doubler rectifier with radial stub filter can provide output DC voltage higher than 7 V. The measured RF-to-DC conversion efficiency of the integrated rectenna is 76.84%. at an input power of 20 dBm. The proposed rectenna has the advantages of harmonic rejection, circular polarization, high gain and low cost which make it a suitable candidate for microwave energy transfer.